From current to future projections: modeling habitat suitability changes for Hibiscus syriacus L. in China using MaxEnt under climate change - Xu, Jing; Zhao, Yanghui; Wang, Chuncheng; Yan, Yadan; Wen, Yafeng (Frontiers in Plant Science, 2025)
Hibiscus syriacus L. (Malvaceae) is widely cultivated for its ornamental value and diverse applications in food, medicine, and textiles. Despite its extensive use, the key environmental factors and geographic patterns influencing its habitat suitability remain poorly understood. We applied the MaxEnt model to assess the current and projected future distribution of H. syriacus using 185 occurrence records and 20 environmental variables. Results showed that the current suitable habitat area covered 188.81 × 104 km². Temperature and precipitation played a crucial role in shaping the present geographical distribution of H. syriacus populations. Projections indicated that by the 2050s, the total suitable habitat area would expand, with the SSP585 scenario demonstrating the most substantial increase. However, a general decline was expected by the 2070s. The potential distribution, primarily concentrated in Hunan Province, was projected to shift southwestward. Migration patterns and habitat changes were primarily driven by substantial variations in temperature and precipitation. These findings highlight the impact of climate change on the habitat suitability of H. syriacus and offer a scientific basis for determining planting zones and strategies.